PORTAL APLIKASI KAJIAN ILMU KEISLAMAN BERBASIS ANDROID PADA MAJLIS TAKLIM DKM NURUL HUDA - Buhori Muslim; Eva Susilawati; Emil Herdiana (JURNAL ILMIAH BETRIK, 2022)
Cianjur as a City of Santri, of course, a lot of Islamic studies are conducted in mosques, mosques, Islamic boarding schools or schools, when these studies are only local in nature and can only be heard by the people around the mosques, Information Technology and Information Systems (ITIS) so far has been understood as the most effective and efficient disseminator of information, of course it can also be an alternative in broadcasting Islamic religious studies so that studies can be heard by anyone anywhere. In making this portal application for Islamic studies, the system development method used, namely the waterfall, the waterfall application in this study is the most suitable because the system is built very systematically and with good accuracy so that a good system is produced and in accordance with the user needs of the application. The application that was built requires computer hardware and Android-based smartphones, where its manufacture begins with analysis and design, the design is modeled with UML and the Java programming language, Android and the database uses Firebase. all tools and features all work. The results of this study are the application portals for the study of Islamic sciences that are most suitable for Android smartphone users.